Governing the Digital Society: Platforms, Artificial Intelligence, and Public Values (Digital Studies, 2025)
Digital technologies have rapidly become integral to communities and societies, bringing both significant benefits and serious concerns. Issues such as misinformation, disinformation, online polarization, discrimination, and widening inequalities have prompted a critical and urgent debate: Can digital societies still be effectively governed? This book brings together insights from various disciplines to address the pressing question: “How can we develop and apply principles of (good) governance in digital societies that are organized democracies?” Governing the Digital Societypresents a range of governance approaches, focusing on online platforms, artificial intelligence, and the public values that underpin these technologies. The authors position themselves at the forefront of their disciplines, offering perspectives from law, critical data studies, urban studies, science and technology studies, computational linguistics, and the political economy of media. Expert interviews provide additional insights into ongoing efforts to tackle the challenges of governing digital societies. The book demonstrates that governance is not just a technical or legal process but a complex societal one, embedding norms, values, and morality into our institutions and daily lives.